Individual differences in age-related neurocognitive outcomes: within-subject assessment of memory for odors - Branch, Audrey E.; Glover, Lucas R.; Gallagher, Michela (Frontiers in Aging Neuroscience, 2023)
Cognitive decline is a common feature of aging, particularly in memory domains supported by the medial temporal lobe (MTL). The ability to identify intervention strategies to treat or prevent this decline is challenging due to substantial variability between adults in terms of age of onset, rate and severity of decline, and many factors that could influence cognitive reserve. These factors can be somewhat mitigated by use of within-subject designs. Aged outbred Long-Evans rats have proven useful for identifying translationally relevant substrates contributing to age-related decline in MTL-dependent memory. In this population, some animals show reliable impairment on MTL-dependent tasks while others perform within the range of young adult rats. However, currently there are relatively few within-subject behavior protocols for assessing MTL function over time, and most require extensive training and appetitive motivation for associative learning. In the current study, we aimed to test whether water maze learning impairments in aged Long-Evans rats would be predictive of delayed recognition memory impairments and whether these odor memory impairments would be stable within subjects over multiple rounds of testing.